ANALYSIS OF THE COSMIC MICROWAVE BACKGROUND SKY FLUCTUATIONS USING THE HOLOGRAPHIC ENTANGLEMENT ENTROPY - Luthfan Prihadi, Hadyan
In this work, analysis of the cosmic microwave background sky fluctuations is done by investigating two-point correlation functions of the holographic entanglement entropy fluctuations. An entangled quantum state stores information about how entangled the state is, described by the von Neumann entropy as the entanglement entropy. A quantum state for N partitions needs a definition of the multipartite entanglement entropy. Explicit calculation of the entanglement entropy in a d-dimensional quantum field theory (CFTd) can be achieved by the AdS/CFT correspondence using the Ryu-Takayanagi equation which calculates a minimal surface in AdSd+1 geometry, analogous with the Bekenstein-Hawking black hole’s entropy. The expansion of the multipartite holographic entanglement entropy around the homogeneous point only shows terms with even exponent numbers and hence the first-order of the holographic entanglement entropy fluctuations has symmetric or Gaussian distribution property. By correlating the change of entropy and temperature using the first law of quantum thermodynamics, the analysis of entropy fluctuation distribution can be used for investigating the temperature fluctuation of the cosmic microwave background sky, which also has the Gaussian distribution property. From that interpretation, writer concludes that quantum physics might play a role in the analysis of the cosmic microwave background fluctuations via entanglement; this result gives a new insight in analyzing the quantum property of a large-scale cosmology.